FEATURES OF THE DEVELOPMENT OF COMMUNICATION SKILLS IN CHILDREN WITH DISORDERS ON THE AUTISM SPECTRUM (Psychology Travelogs, 2024)
An article devoted to this topic may contain useful information about methods of developing communication skills in children with autism spectrum disorders, recommendations for parents and teachers, as well as research results in this area. This information can be important for anyone who works with children with autism or has such children in the family.Features of the development of communication skills in children with autism spectrum disorders is a very important topic for study. Such children cannot properly use visual contact, facial expressions and gestures to coordinate social interactions, and cannot build relationships with peers. They lack social and emotional dependence, lack of shared interest in communicating with other people, relative inability to start or maintain a conversation at any stage of language development, ambiguity of imitation, or complete lack of imitation, inability to reflect, etc.Children with autism may have unique needs and requirements in the development of speech and communication. It is important to understand that communication may be more difficult for these children, but with appropriate support they can make significant progress in this area. To solve this problem, it is necessary to develop a step-by-step action plan, in which the communicative activity of a child with autism spectrum disorders will gradually develop, in various simulated and natural situations, and will continue in the child's daily activities.Using techniques to develop communication skills, such as natural communication methods, positive reinforcement, and the use of different communication tools (such as communicators or assistive communication devices), can be very helpful for children with autism. Moreover, early development of communication skills and access to specialized care can significantly improve the quality of life of these children and help them successfully integrate into society.
Keywords: autism spectrum disorders; communication skills; communication development; alternative methods of communication; psychological assistance